Association between the use of electronic cigarettes and subsequent initiation of tobacco cigarettes in the youth population of a city: A retrospective cohort study - Khadeejah Hussain; Sancheti P. V.; Agrawal M; Parande M. A.; Tambe M. P.; Borle P (Journal of Krishna Institute of Medical Sciences University)
Background: Previous use of electronic cigarettes has shown to open a gateway for subsequent initiation of combustible cigarettes in the youths. Aim and Objectives: This study aimed to compare the incidence of subsequent initiation of smoking combustible cigarettes among the E-cigarette users and E-cigarette non-users in the age group of 16 to 25 years. Further, the role of various factors which led to the initiation of smoking combustible cigarettes in E- cigarette users was studied. Material and Methods: A retrospective cohort study was conducted among youths from general population for a duration of 4 months in a metro city. Cohort of youths (age group of 16 to 25 years) using E- cigarette and not using E-cigarette were taken as subjects. Subjects were interviewed using an approved questionnaire containing sections about demographic data, details of behaviours related to E-cigarette use. Results: Those who had previous E-cigarette exposure had 7.27 times the risk of subsequent initiation of combustible cigarettes than those who did not have previous E-cigarette exposure (Relative Risk = 7.27). In present study, 'Curiosity' stood out as the factor reported by most (70.45%) of the participants, which led to the initiation of smoking combustible cigarettes in E-cigarette users, followed by 'Adventure' (40.91%), 'Peer Pressure' (31.82%), 'Need for more nicotine' (29.55%) and lastly, 'Stressful life' (25%). Conclusion: The incidence of initiating subsequent combustible cigarette use in E-cigarette users was higher than that in E-cigarette non-users.